Insights into Mechanochemical Reactions at Targetable and Stable, Sub‐ambient Temperatures. (5th September 2018) - Andersen, Joel; Mack, James
Abstract: We provide insights into the effects of stable and verifiable, low‐temperature conditions on mechanochemical reactions. These are made possible by modifications made to a SPEX 8000 m Mixer/mill allowing reliable fine control of low‐temperature mechanochemical reactions. Using the reduction of 4‐tert‐butylcyclohexanone as a model system we find the diastereomeric product distribution bore a strong dependence on the selected temperature. The same reduction in methanol at room temperature shows similar stereoselectivity trends. In both cases decreasing temperature favors increases in selectivity, although the effect is more pronounced in the solvent‐free mechanochemical conditions. These results indicate that the cooled jar provides a heatsink to mitigate the exothermic character of the reaction. Stereoselectivity also showed a dependence on operating frequency, although the nature of this dependence remains unclear. Applications of our reactor extend far beyond what is presented herein. Abstract : In der Kälte gemahlen : Mechanochemische Reaktionen bei tiefen Temperaturen wurden anhand der Reduktion von 4‐ tert ‐Butylcyclohexanon als Modellsystem untersucht und mit entsprechenden Reaktionen mit Methanol bei Raumtemperatur verglichen. Werden Temperatur oder Frequenz variiert, so kommt es in beiden Fällen zu deutlich veränderten Stereoselektivitäten. Der bei diesen Studien eingesetzte Reaktor könnte weitere Anwendungen haben.